VIBRATION DISEASE, ETIOLOGY, TYPES, CLINIC, DIAGNOSTIC METHODS, TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Vibration disease has an occupational character. It develops in workers of manual mechanized labor associated with the use of tools of percussive or rotational nature. Most often vibration disease is found among workers in mining, construction, metallurgy, ship and aircraft construction, transportation industries, as well as in agriculture. The professions that are in the risk group for the development of vibration disease include: drillers, polishers, stone cutters, grinders, asphalt pavers, stump cutters, streetcar drivers and others. Clinical symptoms of vibration disease depend on the frequency of vibration, its nature (general or local) and accompanying factors (noise, forced body position, cooling, etc.).